Decentralization and Natural Disasters - Timothy J. Goodspeed (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper surveys recent research on decentralization and natural disasters. The first part discusses results from theoretical models that have been used to study the issues that arise when natural disasters occur in a country with more than one level of government. The next section discusses the empirical results that have been found in the literature. A third section briefly touches upon practical problems that arise when decentralized governments are confronted with a natural disaster. The paper concludes by reflecting on what we know about whether policies to confront natural disasters should be centralized or decentralized.
Keywords: H54; H79; Q54; R00; 330; natural disasters; decentralization; risk-sharing; redistributive transfers; federalism; intergovernmental relations; grants